How do experts read the Bible? Descriptions of literary and historical approaches to biblical interpretation using thinking-aloud protocols - Tsemach, Ehud (Journal of Religious Education, 2024)
This study describes the thinking strategies and epistemological stances of two Bible experts, who applied a literary and historical interpretive approach, respectively. A thinking-aloud protocols methodology was used as the two scholars read the same biblical story and verbalized their thoughts. The findings reveal intricate relationships between thinking strategies and interpretive approaches. The two scholars use similar thinking strategies, yet apply them within distinct epistemological stances and reading objectives. Both apply close reading; recall commentaries; syntactic and grammatical analysis. Both connect the story with other biblical texts. However, their reading goals differ. One applies strategies that deconstruct the biblical story to different sources and restore the Urtext. The other applies a reading approach that conceives the text as a unified literary work. He constructs possible meanings and messages from the story using literary criticism tools, relating to literary genres, and actualizing the ancient text. I discuss how these findings contribute to the literature about Bible scholarship and religious education and its pedagogical implications.